Comparison of bone marrow versus peripheral blood allogeneic hematopoietic stem cell transplantation for hematological malignancies in adults—a systematic review and meta-analysis. Issue 2 (May 2015) - Holtick, Udo; Albrecht, Melanie; Chemnitz, Jens M.; Theurich, Sebastian; Shimabukuro-Vornhagen, Alexander; Skoetz, Nicole; Scheid, Christof; von Bergwelt-Baildon, Michael
Highlights Peripheral blood stem cells have replaced bone marrow as main stem cell source in the last two decades. Transplant indications, conditioning regimens and donor selection criteria have clearly changed in the last 10–15 years. It is under debate, whether transplant outcomes might be influenced by the choice of the stem cell source against the background of current transplant settings. This systematic review demonstrates that the current clinical standard to use peripheral blood stem cells instead of bone marrow for allo-SCT is not inferior with regard to the primary outcome overall survival although graft-versus-host disease is increased. Data must be collected analysing more recently treated patients with regard to reduced-intensity and mismatch transplants as well as transplants of elderly patients.